Specification of software systems - Alagar, Vangalur S., 1940- (Graduate texts in computer science., 1998)
This graduate-level text provides an introduction to software specification emphasizing formal methods that are relevant to requirements and design stages of software development. The book can also be used as a text for a one-semester course on formal methods at the senior undergraduate level. Readers are assumed to have a working knowledge of software engineering and basic discrete mathematics, but otherwise this may be their first encounter with formal specification.